Introduction to security and network forensics - Buchanan, William J. (Boca Raton, Florida : CRC Press, 2011)
Keeping up with the latest developments in cyber security requires ongoing commitment, but without a firm foundation in the principles in computer security and digital forensics, those tasked with safeguarding our most private information will be lost in a turbulent and shifting sea. Providing such an introductory text, Introduction to Security and Network Forensics covers the basic principles of intrusion detection systems, encryption, and authentication, as well as the key academic principles related to digital forensics.
Introduction to security -- Intrusion detection systems -- Encryption -- Authentication, hashing, and digital certificates -- Enhanced software security -- Network security elements -- Introduction to risk -- Threat analysis -- Network forensics -- Data hiding and obfuscation -- Web infastructures -- Cloud/Grid computing -- Appendix A.
Includes bibliographical references and index.
Keywords: COMPUTER SECURITY